Clinical Outcomes in Diabetic Females Presenting with STEMI: A Cohort Study - Anjana Ajith Beena; Priya Shanmukhan; Veena Felix; Alummoottil George Koshy; Kunjukrishnapilla Sivaprasad (Journal of Clinical and Diagnostic Research)
Introduction: Although the incidence of Acute Coronary Syndrome (ACS) is lower in women, outcomes are worse, particularly in diabetic females. Despite advances in revascularisation and treatment, mortality rates among diabetic females remain higher, with poorer postpercutaneous coronary intervention outcomes. Studies have rarely addressed the differences in the course of myocardial infarction in diabetic females and this underrepresentation has influenced the formulation of guidelines. Aim: To evaluate the in-hospital composite outcomes of death, non fatal myocardial infarction, emergency revascularisation, heart failure and cerebrovascular accident in diabetic women presenting with ST Elevation Myocardial Infarction (STEMI), as well as the individual in-hospital outcomes and outcomes at one and three months follow-up. Materials and Methods: This was a prospective single-centre cohort study conducted between November 2017 and October 2018 on 204 patients with STEMI and followed-up for three months. Data were collected from patients using a semistructured questionnaire-based interview, clinical examination, laboratory investigations, echocardiography and angiography. In-hospital outcomes—death, non fatal MI, emergency revascularisation, heart failure and cerebrovascular accident—were studied. Telephonic follow-up was conducted at one and three months. The comparison of variables was carried out using the Independent Student’s t-test or Chi-square test, and regression analysis was performed to identify predictors of mortality. Results: The mean age was 64±11 years; 60.3% were hypertensive and 26% had dyslipidaemia. A total of 12.3% were newly diagnosed diabetics. The mean prehospital delay was 201.9±156.8 minutes. Primary angioplasty was performed in 77%, while thrombolysis was done in 16.7%. The composite outcome was observed in 26.3% of the patients, with heart failure occurring in 19%, cardiogenic shock in 27.9% and death in 16.2%. Cerebrovascular accidents were noted in 0.5% and renal dysfunction was present in 13.2%. At one and three months, heart failure occurred in 7.6% and 5.8%, respectively. Among those with in-hospital mortality, a higher proportion had Anterior Wall Myocardial Infarction (AWMI) (p=0.043), were in Killip class>II (p-value <0.0001), and had qRBBB (Right Bundle Branch Block) (p-value <0.0001). They presented later, with higher blood sugar (p-value <0.0001) and creatinine values (p-value=0.009) and had a lower Ejection Fraction (EF) (p-value=0.003). Killip class (OR=16.0), presence of Ventricular Septal Rupture (VSR) (OR=23.4), no-reflow phenomenon (OR=23.4) and development of renal dysfunction (OR=9.0) were identified as predictors of mortality. Conclusion: Despite a high rate of revascularisation and fewer procedure-related complications, outcomes remain grim, with a higher incidence of heart failure, cardiogenic shock, renal dysfunction and mortality. A worse clinical profile, left ventricular dysfunction and renal dysfunction were significant predictors of mortality.